Students as Partners: Reflections on a Conceptual Model - Mick Healey; Abbi Flint; Kathy Harrington (Teaching & Learning Inquiry: The ISSOTL Journal, 2016)
This article reflects on a conceptual model for mapping the work which fits under the broad heading of students as partners in learning and teaching in higher education (Healey, Flint & Harrington, 2014). We examine the nature and purpose of the model with reference to specific examples and reflect on the potential and actual uses of the model in the development of practice and policy, focussing particularly on students as co-inquirers in SoTL. The article also provides a framework for the other articles in this special issue.